The Impact of Immune Checkpoint Inhibitors-Induced Skin Toxicity on Patients' Quality of Life and the Role of Dermatologic Intervention - Christina Kemanetzi; Konstantinos Lallas; Elisavet Lazaridou; Chrysoula Papageorgiou; Aimilios Lallas; Alexandros Stratigos; Eleni Timotheadou; George Lazaridis; Dimitrios Dionysopoulos; Kalliopi Kalaitzi; Antonios Tsimpidakis; Myrto Trakatelli; et al. (Mattioli1885, 2024)
Introduction: Data regarding quality of life (QoL) of oncologic patients experiencing dermatologic immune-related adverse events (dirAEs)and their course after dermatologic intervention are scarce. Objectives To assess the impact of dirAEs on patients' QoL and to investigate the correlation between dermatologic and oncologic indexes used for estimating QoL. Methods We enrolled oncologic patients with dirAEs managed in two supportive oncodermatology outpatient clinics in Greece. Patient-reported outcomes included DLQI, EORTC-QLQ-C30 and Numerical Rating Scale for pruritus (pNRS). Results Overall, 110 patients were enrolled in the study. Mean(SD) DLQI and pNRS scores were 15.54 (5.44) and7.25 (2.95), correspondingly, while functional, symptom and summary scores of EORTC-C30 were 79.17 (2.11), 17.66 (3.60) and 80.67 (3.08), respectively. After therapeutic interventions, there was a statistically significant decrease in DLQI scores after1st intervention compared to baseline, and 2nd intervention compared to 1st [mean (SD) decrease 4.38 (2.91), p<0.001 and 5.16 (3.99), p<0.001, respectively]. DLQI showed no correlation with global health status/QoLs (rho 0.01, p=0.90) of EORTC-C30. Conclusions dirAEs negatively affect QoL. Dermatologic intervention improves patients' QoL, facilitating an unimpaired oncologic treatment. Poor correlation between DLQI and EORTC-QLQ-30 highlights the need for adapted QoL measurement tools in the context of ICIs treatment.